2008
DOI: 10.1139/b08-010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological analysis of floral homeotic mutantstepal-like bractandfagopyrum apetalaofFagopyrum esculentum

Abstract: The studies on floral homeotic mutants of the model plant species Arabidopsis thaliana (L.) Heynh. and Antirrhinum majus L. have clarified many important aspects of the genetic control of flower development. However, the details of this process can vary in species representing different lineages of flowering plants. The studies on floral homeotic mutants of nonmodel plant species may significantly improve the understanding of the mechanisms of morphological evolution of flowers. We report here the results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…However, the flower in Polygonaceae is basically apetalous. It can be assumed that in other Polygonaceae such as Fagopyrum (Logacheva et al 2008), B-gene expression is not present in the petaloid perianth, although this has not been verified. Plumbaginaceae have petaliferous flowers with petals arising as appendages from common stamen-petal primordia (De Laet et al 1995).…”
Section: Perianth In the Caryophyllalesmentioning
confidence: 99%
“…However, the flower in Polygonaceae is basically apetalous. It can be assumed that in other Polygonaceae such as Fagopyrum (Logacheva et al 2008), B-gene expression is not present in the petaloid perianth, although this has not been verified. Plumbaginaceae have petaliferous flowers with petals arising as appendages from common stamen-petal primordia (De Laet et al 1995).…”
Section: Perianth In the Caryophyllalesmentioning
confidence: 99%
“…Buckwheat is more closely related to the asterids, which suggests that the control of petal identity by the B-class genes was lost in an ancestor of buckwheat after its divergence from asterids. Earlier, we suggest that B-class genes are not involved in petaloidy in buckwheat based on the phenotype of a buckwheat homeotic mutant (Logacheva et al , 2008); this hypothesis now gains support from the obtained expression profiles. Studies on the complementation of Arabidopsis ap3 and pi mutants via the overexpression of buckwheat AP3 and PI genes also show limited conservation of function (Fang et al , 2015; Fang et al , 2014).…”
Section: Resultsmentioning
confidence: 57%
“…Buckwheat is more closely related to the asterids, which suggests that the control of petal identity by the B-class genes was lost in an ancestor of buckwheat after its divergence from asterids. Earlier, we suggested that B-class genes are not involved in petaloidy in buckwheat based on the phenotype of a buckwheat homeotic mutant ( Logacheva et al, 2008 ). It has carpelloid organs instead of tepals, presumably due to the overexpression of C-class gene(s); in case if B-class genes had been involved these would have been stamens.…”
Section: Resultsmentioning
confidence: 99%